Study of Social and Economic Welfare in the Malang City - Kustiandi , Januar; Rachmawati, Dian (KnE Social Sciences, 2020)
This study aims to determine the level of community welfare, causes of welfare, and efforts made to improve the welfare of the community in Malang. Data analysis is guided by interactive data analysis model. While to know the policy strategy that can be taken by government by using SWOT analysis. The results of this study indicate that the level of welfare of the community in the city of Malang has improved quality, which is indicated by the decrease in pre-prosperous family level. This is supported by the role of government, private, and universities that contribute in the form of providing basic services (health and education) for free for indigenous people of Malang City by the government. In addition, community service programs conducted by the university, also able to improve the quality of human resources community. While the private sector contributes in the form of CSR funds that are used to increase public facilities and infrastructure development and scholarships. Keywords: social welfare, economic prosperity